Prevalence and predictors of lower urinary tract symptoms in Pakistani men: A cross-sectional study. (July 2019) - Salman, M; Khan, JH; Khan, AH; Sulaiman, SAS; Aslam, Z; Asif, N; Mustafa, ZU; Hassan, M; Saleem, Z; Iqbal, M
Objective: The purpose of this study was to investigate the prevalence and severity of the condition of lower urinary tract symptoms in Pakistani men, determine its predictors and assess its impact on the quality of life. Methods: A cross-sectional, population-based study was conducted among men aged 30 years and over in three districts of Punjab province, Pakistan. The modified Urdu version of the International Prostate Symptom Score was used to assess the prevalence and severity of lower urinary tract symptoms. Individuals with total symptom score ⩾8 were considered as having lower urinary tract symptoms. The data were analysed using SPSS version 22. The chi-square test and Mann-Whitney U test were used to assess the difference among categorical and continuous variables, respectively. Moreover, binary logistic regressions were performed to determine the predictors of lower urinary tract symptoms. Results: The overall prevalence of lower urinary tract symptoms in our sample was 33.7%. The frequency of individuals having mild, moderate and severe lower urinary tract symptoms was 66.3, 30.3 and 3.4%, respectively. Storage symptoms were more common than voiding symptoms (35.6% vs 28.2%, respectively). Increasing age (one-decade interval age stratum), higher education levels, working status (currently not working), smoking, hypertension, diabetes and renal impairment were positive predictors of lower urinary tract symptoms. Moreover, the condition of lower urinary tract symptoms was associated with a significant reduction in an individual's quality of life. Conclusion: Around one-third of adult Pakistani men suffer from clinically relevant urinary symptoms, with lower urinary tract symptoms sufferers having poor quality of life as compared to non-sufferers. We recommend that the aging population should be made aware of conventional measures to mitigate mild urinary symptoms affecting their routine activities. Level of evidence: 2c